PEMBERDAYAAN MASYARAKAT MELALUI EDUKASI PENGELOLAAN SAMPAH DI KAWASAN EKOWISATA KALI PAPAH - Adiyanto, Okka; Budi Waluyo, Wisnu; Primasari, Isana Arum (HIKMAYO: JURNAL PENGABDIAN MASYARAKAT AMAYO, 2025)
The community service program at Tour Kali Papah (TKP) ecotourism area was carried out to address the problem of unmanaged waste that threatens environmental sustainability and the quality of tourism. The program employed a participatory empowerment approach through socialization, education, and mentoring activities involving local youth community, residents, and visitors. The activities included the delivery of materials on waste management and ecotourism, interactive discussions, demonstrations of waste sorting, and the introduction of the 3R principles (Reduce, Reuse, Recycle). To measure the program’s effectiveness, pre-test and post-test evaluations were conducted. The results showed a significant increase in participants’ knowledge, with the average score rising from 55.3% to 87.8%. Qualitative observations also indicated a strong enthusiasm from participants, with some proposing the formation of waste management groups and the development of recycled products with economic value. This program has proven effective in improving environmental awareness and behavior while opening opportunities for circular economy innovation at the community level. Follow-up programs are recommended to strengthen waste utilization skills and ensure sustainable management of the ecotourism area.